Estudio del proceso de migración en sistemas locales en entornos en la nube, análisis de beneficios, desafíos y lecciones aprendidas en la transición con ISP en la Empresa Jatnet de la ciudad de Babahoyo. - Vera Muñoz, Erick Steeven (2024)
The Babahoyo company Jatnet is migrating its local systems to the cloud through the use of free and paid software, with low-cost subscriptions, seeking to optimize processes and reduce expenses. In this context, the objective of this study is to analyze the migration process in local systems in cloud environments in the Jatnet company of the city of Babahoyo, as well as to identify and evaluate the benefits, challenges and lessons learned in the transition with ISP. . . In this way, we seek to contribute to knowledge in this field and provide recommendations for companies that are in a similar process of migration to the cloud. It was identified that the Jatnet company uses two software, Dropbox and Google Drive, where the first is used for the mass storage of its clients' data and the second is used by the technical staff on a daily basis, with the purpose not to mix information and create a solid and orderly database. However, while migration offers benefits such as scalability and accessibility, it faces challenges such as data security and integration. This study analyzes the migration process, highlights benefits such as reduced operating costs, points out challenges such as data security, and addresses lessons learned to contribute to knowledge in this field. Concluding that migrating information to the cloud has greater benefits and easy adaptation for staff.